Chemical composition and microbiological quality of bee pollen - Lorini, Alexandre; Rosa, Claudineli Cassia Bueno da; Oliveira, Livia Teixeira; Wobeto, Carmen (Scientia Agraria Paranaensis, 2020)
Besides honey and propolis, bee products already well consolidated, pollen also has relevant economic, nutritional and functional value. As the quality of the final product is directly related to the region where it is collected and processed, this work has evaluated the nutritional and microbiological quality of two dehydrated bee pollens from São Paulo state and the other produced by beekeepers from northern of Mato Grosso state, but with no inspection. Physical-chemical and microbiological quality, phenolic composition and mineral profile analysis were performed. It was observed that both pollens presented satisfactory quality regarding protein contents (24.8 ± 2.4 g 100 g-1), total sugars (36.2 ± 1.1 g 100 g-1), lipids (4.0 ± 0.3 g 100 g-1), ashes (2.6 ± 0.05 g 100 g-1), free acidity (238.7 ± 4.5 mEq Kg-1) and pH (4.8 ± 0.03), however regarding the humidity levels (6.6 ± 2.2 g 100 g-1) both samples were not in accordance with recommended by law (<4 g 100 g-1). The bioactive profile has shown a significant amount of phenolic compounds (37.3 ± 1.1 mg GAE g-1) and flavonoids (41.8 ± 2.5 mg QE g-1), besides potential antioxidants around, approximately, 50 and 80%. Microbiological analyzes have revealed low bacterial contamination (≤ 3.6 MPN g-1), molds and yeasts (variation between 1.2x103 and 4x101 CFU g-1), according to values stipulated by the current legislation, being observed the absence of Salmonella sp. and Escherichia coli. The bee pollens investigated have nutritional quality and safety for consumption. However, pollen from São Paulo state showed greater antioxidant potential, probably due to its higher content of phenolics when compared with pollen from Mato Grosso state.